2019
DOI: 10.5858/arpa.2018-0058-ra
|View full text |Cite
|
Sign up to set email alerts
|

Giving and Receiving Effective Feedback: A Review Article and How-To Guide

Abstract: - Medical education literature emphasizes techniques for giving feedback and describes barriers often encountered to feedback exchange in medical practice. Effective feedback requires that the giver, receiver, and environment be carefully considered. Likewise, each of these factors can impose barriers to feedback exchange. Various methods for giving feedback have been described. All feedback should address a specific behavior, be nonevaluative in nature, and be followed by confirmation of understanding and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 35 publications
3
68
0
12
Order By: Relevance
“…If students are trained to use it as a self-assessment rather than selfgrading, it will be a valuable tool. 31,32 As reported in the literature, our results indicated that classroom response systems (clickers), may increase students' abilities to solve problems and think, thus better preparing them for their future careers. This method of learning sharpens students' skills and increases their confidence to professionally argue and debate within a scientific context, helps students and educators assess points of strength and weakness both among students and in the course, and deepens the understanding and application of knowledge rather than operating at the lower levels of Bloom's taxonomy.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…If students are trained to use it as a self-assessment rather than selfgrading, it will be a valuable tool. 31,32 As reported in the literature, our results indicated that classroom response systems (clickers), may increase students' abilities to solve problems and think, thus better preparing them for their future careers. This method of learning sharpens students' skills and increases their confidence to professionally argue and debate within a scientific context, helps students and educators assess points of strength and weakness both among students and in the course, and deepens the understanding and application of knowledge rather than operating at the lower levels of Bloom's taxonomy.…”
Section: Discussionsupporting
confidence: 68%
“…24 As reported in the literature, the results of this study indicate that immediate feedback was a significant part of using clickers. 25 It has been reported that feedback is essential for continuous learning and improvement; 26 it requires skills to deliver and is essential to the quality of learning. 27 Using clickers can overcome students' fears of being evaluated or judged by teachers or peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Studies have identified that feedback was a valuable tool to increase understanding and consolidate information. 42 , 43 Another important aspect of our study was the SPs observation and assessment of the performance of their peers, which helped self-assessment and self-reflection. The usefulness of self-assessment in improving learning has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…When corrective feedback must be delivered, Jug and colleagues recommend framing the feedback from a subjective point of view and limiting feedback to 1 or 2 pieces at a time. 18 Finally, supervisors who are open to receiving feedback from the trainee about their performance will further support normalizing a culture of feedback.…”
Section: Overview Of the Approachmentioning
confidence: 99%